Poly(styrene–maleic anhydride) functionalized graphene oxide. Issue 22 (16th February 2015) - Zhou, Longfei; Liu, Haihui; Zhang, Xingxiang
ABSTRACT In this study, poly(styrene–maleic anhydride) functionalized graphene oxide (SMAFG) was fabricated with in situ polymerization. The sample was characterized with Raman spectroscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, transmission electron microscopy, and ultraviolet–visible absorption. The results of the experiments show that the thermal stability of SMAFG was improved significantly, and it also possessed a good dispersion in N, N‐dimethylformamide, N, N‐dimethylacetamide, aniline, and certain organic solvents. The calculated Hildebrand parameter of SMAFG was 23.8 MPa1/2. This new method will broaden the applications of graphene, and the experiment showed that it could effectively improve the strength of polyamide 6 (PA6) compared with the pure PA6 fiber. The tensile strength of the SMAFG/PA6 composite fiber improved 29%, and the Young's modulus improved 33%, so this kind of functionalized graphene oxide can be used in the preparation of polymeric composites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41987.